Experimental Study on the Unconfined Compressive Strength of Artificially Cemented Sand. (May 2019) - Wang, Xumin; Wang, Cheng; Yi, Zhao
Abstract: Artificially cemented sand sample was prepared by incorporating cement clinker into the standard sand sample. The electron microscopic scanning test (SEM) and the unconfined compressive strength test of the artificial cementation sand sample were carried out, and the microstructure changes before and after the cementation of the sand sample were analyzed. The formula of the unconfined compressive strength of cemented sand samples considering the influence of cement clinker incorporation ratio Cv and curing time t is proposed. Scanning electron microscopy experiments show that as the incorporation ratio increases, the standard sand gap is gradually filled by the cements, and the shape of the cements attached to the surface of the standard sand changes from flocculant filamentous to pellet. The unconfined compressive strength test shows that the axial strain decreases with the increase of the blending ratio, and the brittle fracture is more and more obvious. The fitting formula of the unconfined compressive strength is proved to be reasonable by the experimental data of other scholars.